Feasibility and safety of transperineal prostate biopsy in the era of cognitive magnetic resonance imaging/ultrasound fusion in cancer detection - Zegarra-Montes, Luis (2022)
Objective: To describe the results of transperineal prostate biopsy by fusion of cognitive magnetic resonance imaging and ultrasound in the detection of cancer. Materials and methods: A retrospective case series study conducted at the Delgado Clinic between July 2019 and October 2021. Patients with digital prostate examination and/or abnormal Prostatic Specific Antigen and prostate MRI images with category lesions were included. PI-RADS 4 or 5. Excluding patients with coagulation disorders, rectal injuries, impossibility for abduction, comorbidities for anesthesia. We recorded clinical and demographic characteristics, prostate-specific antigen data, prostate volume, PI-RADS lesions, cancer rates, and complications. Results: 18 patients were evaluated, with a mean age of 69.33 ± 7.67 years. The mean prostate specific antigen was 14.94 ± 12.42 ng/mL. The mean prostate volume was 57.72 ± 28.68 cc. At the digital examination of the prostate, 16/18 (88.88%) patients had suspected cancer. Biopsies in patients with PI-RADS lesions 4 in 6/18 (33.33%) and 5 in 12/18 (66.67%). Biopsy with 19 cores in 6/18 (33.33%) and 16 cores in 12/18 (66.67%) patients. Cancer patients 15/18 (83.33%), all acinar adenocarcinoma, with Gleason 6 in 2/18 (11.11%) and Gleason ≥ 7 in 13/18 (72.22%) patients. Mild complications such as hematuria 1/18 (5.6%), terminal dysuria 8/18 (44.4%) and perineal discomfort 7/18 (38.8%) and none infectious. Conclusions: transperineal prostate biopsy by fusion of cognitive magnetic resonance imaging and ultrasound is feasible, safe, with high positivity rates and without infections.